‘Peace with a Woman’s Face’: Women, Social Media and the Colombian Peace Process - Henshaw,Alexis (2020)
Abstract The idea that men and women approach conflict resolution differently forms the backbone of the international agenda on Women, Peace, and Security (WPS) and is supported by a growing body of scholarship in international relations. However, the role of women who represent insurgent groups in peace talks remains understudied, given the relatively rare appearance of such women in peace processes. The present study examines how men and women from the negotiating team of the Revolutionary Armed Forced of Colombia (FARC) engaged in public-facing discourse on Twitter leading up to a referendum on the peace accords in 2016. Using a mixed-methods approach that includes computational analysis and a close reading of social media posts, I demonstrate that women in the FARC’s negotiating team were more successful social media users than their male counterparts and that they offered a distinct contribution to the discourse on peace, centring the relevance of gender and promoting issue linkages like the need to address LGBTI rights.